enerapan Pembelajaran Inkuiri Mata Pelajaran Sejarah Kebudayaan Islam di Madrasah Ibtidaiyah Darussalam: Application of Inquiry Learning in Islamic Culture History Subject at Madrasah Ibtidaiyah Darussalam - Rosideh, Rosideh (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study aims to examine the effectiveness of the application of inquiry learning approach in improving students' understanding and active participation in the subject of Islamic Culture History (SKI) at Madrasah Ibtidaiyah Darussalam. The method used was Classroom Action Research (PTK) model of Kemmis and McTaggart, which was implemented in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The research subjects were 26 grade V students. Data collection techniques included observation, formative tests, and interviews. The results showed that the application of inquiry learning was able to increase students' active involvement in the learning process and improve learning outcomes. The students' average score increased from 65.3 in cycle I to 84.3 in cycle II. This finding shows that the inquiry approach is an effective learning strategy in improving the quality of the process and student learning outcomes in SKI learning at the Madrasah Ibtidaiyah level.